2011
DOI: 10.1139/x11-019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspect and type of competition on the early performance of Nothofagus dombeyi and Nothofagus nervosa in a mixed plantation

Abstract: In the Andes of Chile, two valuable Nothofagus tree species coexist (Nothofagus dombeyi (Mirb.) Oerst. and Nothofagus nervosa (Phil.) Krasser). They could provide an opportunity for mixed plantations because of their ecological differences. In a mixed plantation with a checkerboard design on a good site where the two species naturally coexist, we evaluated their performance according to aspect and type of competition. Nothofagus dombeyi had a greater survivorship (90% vs. 65%) and growth (twice in diameter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
(36 reference statements)
2
12
0
4
Order By: Relevance
“…3). For example, N. dombeyi had a higher growth plasticity to resource limitation than N. alpina, as the latter is commonly found on sites of relatively higher quality (sensu Donoso et al 1999Donoso et al , 2011Donoso and Soto 2010), suggesting that species adapted to better sites are more sensitive to detrimental soil conditions (Donoso et al 2011;Soto et al 2014). The difference in plasticity is reflected in both parameters of the Michaelis-Menten model (Table 2).…”
Section: Differential Effects Of Light Availability and Soil Compactimentioning
confidence: 96%
“…3). For example, N. dombeyi had a higher growth plasticity to resource limitation than N. alpina, as the latter is commonly found on sites of relatively higher quality (sensu Donoso et al 1999Donoso et al , 2011Donoso and Soto 2010), suggesting that species adapted to better sites are more sensitive to detrimental soil conditions (Donoso et al 2011;Soto et al 2014). The difference in plasticity is reflected in both parameters of the Michaelis-Menten model (Table 2).…”
Section: Differential Effects Of Light Availability and Soil Compactimentioning
confidence: 96%
“…Even if the volume of the plants is similar in both situations, they grow less vigorously in smaller gaps. Nothofagus nervosa is semi-tolerant to shade, being favoured by partial shade conditions instead of open areas (Veblen et al, 1981;Donoso et al, 2006). In this study, the best development occurs in large gaps, although its opening is around 50%, equivalent to partial shade conditions.…”
Section: Growth Behaviour Of Nothofagus Nervosa Plantations In the Gapsmentioning
confidence: 55%
“…Eventhough the N. nervosa plantation presents a high survival after 11 months of being established, its growth is moderate compared to other sites. For the first year in Valdivia Province, there are growth records of 6.0 mm in diameter and 52 cm in height in the Central Valley and growht of 8.4 mm in diameter and 69 cm in height in the Coastal Range (Donoso et al, 1999); also height growht > 50 cm (Donoso et al, 2006), and height growht between 60 and 70 cm in the Valdivian Andes (650 m asl) (Donoso et al, 2009). Still, the sites in this study have a more restrictive climate, with plants remaining five to six months under the snow.…”
Section: Growth Behaviour Of Nothofagus Nervosa Plantations In the Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not evaluate the growth under very open canopies (>60%). However, Donoso et al [65] and Soto et al [10,35] showed that greater growth rates in Raulí occur in open fields when planted with neighboring faster-growing evergreen species (i.e., facilitation mechanisms under partial shade). In addition, Donoso et al [9,45] showed that the growth in Raulí was indifferent to canopy openness during the seedling stages but during the sapling stages, growth was enhanced with increased light.…”
Section: Implications For Forests Restorationmentioning
confidence: 99%